Design for Customer - Methodik für nachhaltige Kundenlösungen unter Zuhilfenahme eines bedürfnisorientierten Leistungskonfigurators - Burger, Alexander (Reihe Informationsmanagement im Engineering Karlsruhe / Hrsg.: Karlsruher Institut für Technologie, Institut für Informationsmanagement im Ingenieurwesen (IMI), 2016)
Increasing competitive pressure and the internationalization of markets represent actual challenges for global acting companies. One possibility to meet these challenges is the provision of product-service-systems. The developed methodology provides an approach for integrating the customer into the processes of product-service-system providers. In addition to the differentiation from the competition, it also enables an increase in sales and profit margin.